Distribution models predict large contractions of habitat‐forming seaweeds in response to ocean warming. Issue 10 (26th September 2018) - Martínez, Brezo; Radford, Ben; Thomsen, Mads S.; Connell, Sean D.; Carreño, Francisco; Bradshaw, Corey J. A.; Fordham, Damien A.; Russell, Bayden D.; Gurgel, C. Frederico D.; Wernberg, Thomas
Abstract: Aim: Understanding the relative importance of climatic and non‐climatic distribution drivers for co‐occurring, functionally similar species is required to assess potential consequences of climate change. This understanding is, however, lacking for most ecosystems. We address this knowledge gap and forecast changes in distribution for habitat‐forming seaweeds in one of the world's most species‐rich temperate reef ecosystems. Location: The Great Southern Reef. The full extent of Australia's temperate coastline. Methods: We assessed relationships between climatic and non‐climatic environmental data known to influence seaweed, and the presence of 15 habitat‐forming seaweeds. Distributional data (herbarium records) were analysed with MAXENT and generalized linear and additive models, to construct species distribution models at 0.2° spatial resolution, and project possible distribution shifts under the RCP 6.0 (medium) and 2.6 (conservative) emissions scenarios of ocean warming for 2100. Results: Summer temperatures, and to a lesser extent winter temperatures, were the strongest distribution predictors for temperate habitat‐forming seaweeds in Australia. Projections for 2100 predicted major poleward shifts for 13 of the 15 species, on average losing 78% (range: 36%–100%) of their current distributions under RCP 6.0 and 62% (range: 27%–100%) under RCP 2.6. The giant kelp ( Macrocystis pyrifera) and three prominent fucoids ( Durvillaea potatorum, Xiphophora chondrophylla and Phyllospora comosa ) were predicted to become extinct from Australia under RCP 6.0. Many species currently distributed up the west and east coasts, including the dominant kelp Ecklonia radiata (71% and 49% estimated loss for RPC 6.0 and 2.6, respectively), were predicted to become restricted to the south coast. Main conclusions: In close accordance with emerging observations in Australia and globally, our study predicted major range contractions of temperate seaweeds in coming decades. These changes will likely have significant impacts on marine biodiversity and ecosystem functioning because large seaweeds are foundation species for 100s of habitat‐associated plants and animals, many of which are socio‐economically important and endemic to southern Australia.